Effects of moxonidine injected into rostral ventrolateral medulla on blood pressure, heart rate, and renal sympathetic nerve activity in rats - Xu Yan-Fang; He Rui-Rong (Acta Pharmacologica Sinica; Vol 18, No 5 (September 1997): Acta Pharmacologica Sinica, 2016)
AIM: To examine the effects of moxonidine (Mox) injected into the rostral ventrolateral medulla (RVLM) on blood pressure (BP), heart rate (HR), and the renal sympathetic nerve activity (RSNA) in anesthetized normotensive rats. METHODS: BP, HR, and RSNA were simultaneously recorded after 1 microL Mox 1, 10, and 100 mumol.L-1 was injected into RVLM. RESULTS: Mox 1, 10, and 100 mumol.L-1 reduced BP from 13.9 +/- 1.0 kPa to 13.0 +/- 1.7 kPa (P < 0.05), 13.8 +/- 1.8 kPa to 11.4 +/- 1.5 kPa (P < 0.01), and 13.9 +/- 1.9 kPa to 9.4 +/- 1.7 kPa (P < 0.01), respectively. Mox did not influence HR. RSNA varied with the doses: Mox 1 mumol.L-1 increased RSNA by 50% (P < 0.05), 10 mumol.L-1 insignificantly influenced RSNA (P > 0.05), and 100 mumol.L-1 reduced RSNA by 23% (P < 0.05). In sinoaortic barodenervated rats, Mox 10 mumol.L-1 inhibited RSNA by 50% (P < 0.05), which substantially differed from that in buffer nerve intact rats (P < 0.01). CONCLUSION: Mox injected into RVLM decreased BP, but did not influence HR. The changes of RSNA did not parallel with the depressor effect of Mox.